Financing obstacles and growth: an analysis for euro area non-financial corporations - Chiara Coluzzi; Annalisa Ferrando; Carmen Martinez-Carrascal (European Central Bank (ECB), 2009)
This paper investigates whether financial obstacles, and, more generally, financial pressure faced by firms, significantly affect firm growth. For this purpose, we use an unbalanced panel of about 1,000,000 observations for around 155,000 non-financial corporations in five euro area countries. In addition to the balance sheet information in this panel, we also rely on firm-level survey data. In this way we are able to work out a direct measure of the firms' probability of facing financing obstacles. Our results indicate that, though based on few variables, this measure appears to be relevant in explaining firm growth in four out of the five countries considered. Other firm-level variables related to the financial pressure faced by firms, such as cash flow (debt burden) are found to exert a positive (negative) impact on firm growth, while the results for leverage are less clear-cut.
Keywords: C23; E22; G32; L11; L25; 330; Financing Constraints; Firm Growth; panel data; Unternehmenswachstum; Unternehmensfinanzierung; Kapitalstruktur; KMU; Panel; Eurozone